2020
DOI: 10.1111/jocn.15150
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress facing nurse academics—A mixed‐methods systematic review

Abstract: Aim To better understand occupational stress faced by nurse academics. Methods A mixed‐methods systematic review, following the Joanna Briggs Institute [JBI], (Joanna Briggs Institute Reviewers’ Manual: 2014 edition, 2014) process. Studies were assessed for quality and risk of bias by using standardised critical appraisal instruments from the Joanna Briggs Institute. In addition, processes and reporting were checked against the Equator guidelines. See Appendix S1. Results The review revealed that nursing acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 50 publications
(160 reference statements)
2
95
1
Order By: Relevance
“…Sarafis et al [18] supported these findings, but Godwin et al [19] found a significant association between occupational stress and work experience. One of the important effective factors in reducing the occupational stress in nurses is to improve their levels of knowledge, attitude, and practice with regard to the principles of clinical care, which is called 'professionalism' in the nursing profession [1]. Considering the findings of this study, it seems that the participants were not professional in their nursing occupation and still had stress like novice nurses.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Sarafis et al [18] supported these findings, but Godwin et al [19] found a significant association between occupational stress and work experience. One of the important effective factors in reducing the occupational stress in nurses is to improve their levels of knowledge, attitude, and practice with regard to the principles of clinical care, which is called 'professionalism' in the nursing profession [1]. Considering the findings of this study, it seems that the participants were not professional in their nursing occupation and still had stress like novice nurses.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies reported that occupational stress was moderately high in ICU nurses [9,11,14], which is in line with the findings of the present study. A mixed-method study in America indicated that occupational stress was prevalent in nurses and its long-term sustainability could have a negative impact on nurses' health [1]. Moderate-high occupational stress among ICU nurses can be justified by their critical working conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Many studies showed that ongoing exposure to occupational stress can result in job burnout, which can affect physical, psychological and social health. 46,47 A large number of studies observed that the effects of burnout syndrome might affect nurses' mental health, and there were also some evidence verifying that burnout had bad impact on people's physical health. 48,49 Job burnout may lead to helplessness, despair, sleep problems, and exhaustion and ultimately affect physical and mental health, which are highly associated with QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed at the University of Surrey, although Rounds were initially run for academic colleagues, so that they would understand what they were and could promote them to students, the stories of stress and burnout shared by academic staff made us realise academic health sciences staff needed Rounds too. Recent research supports this highlighting the challenges faced by staff in HE institutions in health care (with nurse academics’ well‐being impacted with burnout and stress threatening the sustainability of the academic workforce (Singh, Cross, Munro, & Jackson, 2019)). If nurse academics were already overstretched (increased student numbers, additional administrative tasks and extreme working hours), the need to revise and rewrite their education programmes as COVID‐19 moves swiftly through our communities has increased working hours and stress levels substantially.…”
Section: Origins Of Schwartz Rounds In the Usa And Uk Nhs And Introdumentioning
confidence: 95%